Having a Coffee Break: The Impact of Caffeine Consumption on Microglia-Mediated Inflammation in Neurodegenerative Diseases - Maria H. Madeira; Raquel Boia; António F. Ambrósio; Ana R. Santiago (Hindawi Limited, 2017)
Caffeine is the major component of coffee and the most consumed psychostimulant in the world and at nontoxic doses acts as a nonselective adenosine receptor antagonist. Epidemiological evidence suggests that caffeine consumption reduces the risk of several neurological and neurodegenerative diseases. However, despite the beneficial effects of caffeine consumption in human health and behaviour, the mechanisms by which it impacts the pathophysiology of neurodegenerative diseases still remain to be clarified. A promising hypothesis is that caffeine controls microglia-mediated neuroinflammatory response associated with the majority of neurodegenerative conditions. Accordingly, it has been already described that the modulation of adenosine receptors, namely, the A2A receptor, affords neuroprotection through the control of microglia reactivity and neuroinflammation. In this review, we will summarize the main effects of caffeine in the modulation of neuroinflammation in neurodegenerative diseases.